1996
DOI: 10.1180/minmag.1996.060.403.07
|View full text |Cite
|
Sign up to set email alerts
|

Sericitization of plagioclase in the Rosses Granite Complex, Co. Donegal, Ireland

Abstract: Sericitization in three separate pulses of the Rosses Granite Ring Complex, Co. Donegal, Ireland, has been investigated texturally and chemically using electron microscopy, electron microprobe and fluid inclusion thermometry. The sericitization, which is restricted to the cores of plagioclase, is associated with pores which are abundant in the cores, but absent in the margins. Alkali feldspar, although porous, is unaltered. Associated with the sericitization is alteration of the adjacent primary plagioclase wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
3

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 27 publications
0
19
0
3
Order By: Relevance
“…The widespread appearance of sericite suggests that the process of sericitisation occurred during the final stages of crystallisation (deuteric alteration) rather than during a more localised hydrothermal alteration (Speer, 1984;Que & Allen, 1996). The sericitisation process is characterised by the replacement of plagioclase by sericite and the replacement of Ca 2+ by Na + , and is thus often concentrated in the more anorthitic zones of the plagioclase crystal (Que & Allen, 1996). The process can be coupled with the transformation of biotite to chlorite (Speer, 1984;Eggleton & Banfield, 1985;Que & Allen, 1996).…”
Section: Pre-permianmentioning
confidence: 99%
See 1 more Smart Citation
“…The widespread appearance of sericite suggests that the process of sericitisation occurred during the final stages of crystallisation (deuteric alteration) rather than during a more localised hydrothermal alteration (Speer, 1984;Que & Allen, 1996). The sericitisation process is characterised by the replacement of plagioclase by sericite and the replacement of Ca 2+ by Na + , and is thus often concentrated in the more anorthitic zones of the plagioclase crystal (Que & Allen, 1996). The process can be coupled with the transformation of biotite to chlorite (Speer, 1984;Eggleton & Banfield, 1985;Que & Allen, 1996).…”
Section: Pre-permianmentioning
confidence: 99%
“…The sericitisation process is characterised by the replacement of plagioclase by sericite and the replacement of Ca 2+ by Na + , and is thus often concentrated in the more anorthitic zones of the plagioclase crystal (Que & Allen, 1996). The process can be coupled with the transformation of biotite to chlorite (Speer, 1984;Eggleton & Banfield, 1985;Que & Allen, 1996). The chloritisation corresponds to the alteration of biotite manifested by the change in colour from brown to green along the 001 plane as observed under the optical microscope and the concurrent depletion of K + as discovered by the SEM-EDS analysis (e.g., Fig.…”
Section: Pre-permianmentioning
confidence: 99%
“…Discussion of structural and petrologic record 5.1. Geometry of the veins and implications for stress field and level of emplacement Owing to incomplete reactions and widespread disequilibrium in the alteration zone, the level of vein emplacement can hardly be constrained by thermobarometry based on mineral phase equilibria In view of the K-feldspar in perthite transformed to microcline, sericitisation of plagioclase and newly formed biotite, a broad range of temperatures between about 300 and 500 8C appears feasible (Que and Allen, 1996;Parson and Lee, 2000). Temperatures near 500 8C must have been reached for a short time at the contact with the intruding pegmatitic melt, with a temperature of at least 650 8C, and the hot fluids liberated from the magma upon solidification.…”
Section: Microcrack Density As a Function Of Distance From The Centramentioning
confidence: 99%
“…A number of studies have reported that the alteration of plagioclase is mainly related to the activity of hydrothermal fluid (e.g., Fournier, 1965;Page and Wenk, 1979;Peters and Hofmann, 1984;Kamineni et al, 1993;Que and Allen, 1996). During fieldwork examining granitic rocks and their constituent minerals within the Takakumayama district, Kagoshima Prefecture, Japan, pink altered plagioclases up to 5 mm long were observed within the Honjo River in the Sarugajo Valley.…”
Section: Introductionmentioning
confidence: 99%